FITOREMEDIASI TANAH TERCEMAR MERKURI MENGGUNAKAN Lindernia crustacea, Digitaria radicosaa, DAN Cyperus rotundus SERTA PENGARUHNYA TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN JAGUNG - Bonauli Christianoyd Siahaan; Sri Rahayu Utami; Eko Handayanto (Jurnal Tanah dan Sumberdaya Lahan, 2014)
Levels of heavy metals in agricultural land can be reduced and neutralized with an inexpensive method, known as phytoremediation. The purpose of this study was to learn and know the ability Lindernia crustaceans, Digitaria radicosa, and Cyperus rotundus as fitoremediator for soil contaminated by gold mining waste containing mercury and its effects on growth and yield of maize The study was conducted in a glasshouse with sixteen treatments consisted of three plant accumulators, two soils contaminated with mercury, and two levels of organic matter application. The parameters measured were plant height, number of leaves, dry weight, crop N uptake,Â  Hg content, and uptake of Hg. The results showed that 10% of tailings contaminated soil (T1) contained Hg less than 20% of tailings contaminated soil (T2). The addition of organic material could assist in providing the nutrients needed by plants to improve soil fertility, so the potential for increased uptake and could reduce the content of Hg in tailing contaminated soil. Lindernia crustacea, Digitaria radicosa, and Cyperus rotundus are potential in reducing mercury concentration in tailing contaminated soils that in turn improved maize growth.